(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The purpose of the study was to produce infant clothing articles using fabric waste and patchwork technique. Specifically, the study sought to: produce five infant clothing articles using fabric waste and patchwork technique for various infant activities and assessed the appropriateness of infant clothing articles produced from fabric waste using patchwork technique based on functional, expressive and aesthetic attributes. The study was guided by three hypotheses. The study was undertaken in two phases. The research and development design were adopted for phase I while a descriptive survey design was utilized for phase II of the study. Purposive sampling technique was used to select 15 judges for the study. infant clothing article assessment instrument for judges (ICAAIJ) was used in phase two of the study for data collection. The reliability of the instrument was determined using Cronbach Alpha coefficient which yielded as follows: functional attribute= 0.84, expressive attribute = 0.90 and aesthetic attribute =0 .82.ANOVA were used to test the hypotheses at 0.05 level of significance. Findings revealed that judge’s acceptance was significantly related to aesthetic, expressive and functional attributes of infant clothing articles produced. Among recommendations made were that Schools in Rivers State should set up practical fabric recycling programmes and activities in schools to enlightened and encourage students on fabric waste utilization and that lecturers in the Department of Home Economics in tertiary institutions should carry out more practical work on utilization of fabric waste for the production of useful articles using different clothing construction techniques.